Access to Justice for Workers Irregularly Dismissed in the 1990s and Compensatory Benefits Today - Huancapaza Hilasaca, Joel Emerson (2024)
The purpose of analyzing, on the one hand, the fundamental right of access to justice for workers irregularly dismissed in the 1990s and, on the other hand, the situation at the judicial level of the Extraordinary Program of Access to Benefits for former workers who appear in the National Registry of Irregularly Terminated Workers, is to articulate the law with the facts in light of new challenges that labor justice has for the comprehensive reparation of the victims, knowing that, due to their vulnerability, the plaintiff in the process is an older adult who exercises his or her rights before the justice system.